Aviso de $\ 13\mid n\,10^{\large 9}\!+n = n(\color{#c00}{10^{\large 9}\!+1})\,\ $ $\,\ {\rm mod}\ 13\!:\, \overbrace{\color{#c00}{10^{\large 9}}\equiv ((-3)^{\large 3})^{\large 3}}^{\Large (10\ \ \,\equiv\,\ \ -3)^{\,\Large 9}\quad\ \, }\!\!\equiv (-1)^{\large 3}\equiv\,\color{#c00}{-1}$
Comentario $\ $ En la misma forma en la que podemos ver rápidamente que $\,7,11,19\mid 10^{\large 9}+1$
$\qquad \a la izquierda.\begin{align}
{\rm mod}\ \ 7\!:&\,\ \color{#c00}{10^{\large 3}}\ \equiv\,\ 3^{\large 3}\,\ \equiv\,\ \color{#c00}{{-}1}\\ \\
{\rm mod}\ 11\!:&\,\ \color{#c00}{10^{\large 3}}\equiv (-1)^{\large 3}\equiv\color{#c00}{-1}
\end{align}\right\}\ \Rightarrow\, 10^{\large 9}\equiv (\color{#c00}{10^{\large 3}})^{\large 3}\equiv (\color{#c00}{-1})^3\equiv -1$
$\qquad {\rm mod}\ 19\!:\ 10^{\large 9}\equiv (-3^{\large 2})^{\large 9}\equiv -3^{\large 18}\equiv -1\ $ a poco de Fermat